A novel approach to characterize phenotypic variation in GSD IV: Reconceptualizing the clinical continuum - Bridget T. Kiely; Rebecca L. Koch; Leticia Flores; Danielle Burner; Samantha Kaplan; Priya S. Kishnani (Frontiers in Genetics, 2022)
Purpose: Glycogen storage disease type IV (GSD IV) has historically been divided into discrete hepatic (classic hepatic, non-progressive hepatic) and neuromuscular (perinatal-congenital neuromuscular, juvenile neuromuscular) subtypes. However, the extent to which this subtype-based classification system accurately captures the landscape of phenotypic variation among GSD IV patients has not been systematically assessed.Methods: This study synthesized clinical data from all eligible cases of GSD IV in the published literature to evaluate whether this disorder is better conceptualized as discrete subtypes or a clinical continuum. A novel phenotypic scoring approach was applied to characterize the extent of hepatic, neuromuscular, and cardiac involvement in each eligible patient.Results: 146 patients met all inclusion criteria. The majority (61%) of those with sufficient data to be scored exhibited phenotypes that were not fully consistent with any of the established subtypes. These included patients who exhibited combined hepatic-neuromuscular involvement; patients whose phenotypes were intermediate between the established hepatic or neuromuscular subtypes; and patients who presented with predominantly cardiac disease.Conclusion: The application of this novel phenotypic scoring approach showed that–in contrast to the traditional subtype-based view–GSD IV may be better conceptualized as a multidimensional clinical continuum, whereby hepatic, neuromuscular, and cardiac involvement occur to varying degrees in different patients.